2019
DOI: 10.1111/crj.13107
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and health‐related quality of life among patients with chronic obstructive pulmonary disease in China

Abstract: Objectives Fatigue is an important yet ignored symptom of chronic obstructive pulmonary disease (COPD). However, there is a paucity of literature from China on fatigue and its association with health‐related quality of life (HRQoL) among COPD patients. The purpose of this study was to (a) evaluate fatigue of COPD inpatients in China and (b) explore the association between fatigue and HRQoL. Methods This cross‐sectional study recruited patients hospitalised for an acute exacerbation of COPD within one month fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The prevalence of moderate to severe fatigue was 48.88% in COVID-19 patients, which was consistence with the COPD patients admitted to hospitals with an acute exacerbation, which is a more severe group of patients [15] .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The prevalence of moderate to severe fatigue was 48.88% in COVID-19 patients, which was consistence with the COPD patients admitted to hospitals with an acute exacerbation, which is a more severe group of patients [15] .…”
Section: Discussionmentioning
confidence: 88%
“…The 9-item Functional Assessment of Chronic Illness Therapy-Fatigue scale (FACIT-F) was demonstrated to be reliable and valid for measuring COPD-related fatigue [14,15] .The 9-item FACIT-F scale consists of three components: general fatigue (5 items), functional ability (2 items) and psychological fatigue (2 items). Each item is rated from 0 to 4 and the overall score ranges from 0 to 36, with a higher score signifying less fatigue [16] .We applied the cut-off of 12 and 24 points, thus patients' fatigue degree was classi ed as mild (FACIT-F score 24 to 36), moderate (12 to 23) and severe (0 to 11).…”
Section: Assessment Of Chronic Illness Therapy-fatigue Scalementioning
confidence: 99%
“…In addition to the assessment method, the characteristics of the different study populations also contributed to the difficulty of interpreting the differences in prevalence rates between the studies. For example, the lowest prevalence rate (17%) was observed in a study by YANG et al [24], who studied fatigue in a sample of 210 patients with COPD hospitalised for acute exacerbations of chronic obstructive pulmonary disease (AECOPD) during the moment of inclusion. In contrast, the highest prevalence of fatigue (95%) was reported by KINSMAN et al [40], who examined fatigue in patients during hospital stays in which patients were asked about occurrence of fatigue during breathing difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue can have major consequences on health status, as it may restrict patients' daily activities, lead to a worsened prognosis and is a predictor of mortality [5]. study was carried out in primary care settings [20], sixteen studies in secondary care settings [6,16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34], three studies were in pulmonary rehabilitation settings [35][36][37], two studies in tertiary care settings [38,39], and one study had a mixed population from secondary and tertiary care settings [40]. Only two studies used validated cut-offs to determine prevalence referring to normal, mild and severe fatigue [6,27].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in HRQoL in association with physical activity were reported in seven publications using SGRQ, CAT, SF-12, CCQ, and SF-36. 19,[34][35][36][37][51][52][53] A strong relationship was reported between physical activity and HRQoL, as determined by the association with the number of steps/ day and SGRQ activity scores in patients who were physically active compared with those who were not. 52 Ramon et al performed a pooled analysis investigating the usefulness of self-reported walking time to identify patients with COPD at high risk of inactivity and determined that selfreported walking time decreased with an increase in CAT score.…”
Section: Physical Activitymentioning
confidence: 99%